IMPLEMENTASI PROGRAM KOTA LAYAK ANAK DALAM UPAYA PEMENUHAN HAK-HAK ANAK DI KOTA BEKASI - Elizabeth, Andriani; Hidayat, Zainal (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2016)
The implementation of child-friendly city program is a step to create an environment to ensure the fulfillment of the children rights which are implemented by stakeholders, which is the government, society, and the business industry. The objective of this study is to describe how the implementation of Child-Friendly City Program in fulfilling the rights of children in Bekasi that can be assessed through five indicators which are in the five clusters of the children rights. Researcher analyzed the factors that support and obstruct the programs with six factors were found in the field consist of internal and external factors. The factors are resource, the commitment of officials and policy implementers, communication, society and business industry. The result of this research in attempt to fulfill the rights of children in Bekasi is still encountering obstacles on several clusters. There must be an improvement in resources aspect both in quantity and quality. The communication between the policy implementers have not been good and the information has not been delivered to the target group. The commitment of the officials and all of the policy implementers is still weak.